Pengaruh Realisasi Anggaran, Law Enforcement, Tingkat Kepatuhan, dan Tingkat Inflasi terhadap Penerimaan Pajak - Julaika Putri Rohkhayatim (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Our Country has remained standing and sovereign for more than 75 years, and that cannot be separated from the role of national development efforts that have continued to this day. Sustainable national development in Indonesia is certainly greatly influenced by the performance of tax revenues, considering that tax revenues are the backbone of the state budget in carrying out its functions. Thus, it is necessary to explore more extensive and intensive sources of tax revenue, one of which is by conducting a study of the factors that affect tax revenue. This study aims to analyze the factors that influence tax revenue, in terms of internal Indonesian tax revenue institutions, namely the budget realization of the Directorate General of Taxes (DGT), then in terms of tax law enforcement efforts (Law Enforcement), and in terms of the level of tax law enforcement. Taxpayer compliance, namely the level of compliance with the submission of the Annual Income Tax Return by the Taxpayer. In addition, this study also analyzes one of the effects of macroeconomic factors on tax revenue, namely the inflation rate. The analysis in this study was conducted on 32 observation periods with quarterly time series data obtained from the DGT, starting from 2013 Q1 to Q1. 2020 Q4. This research is a quantitative research with Auto Distributive Lag (ARDL Method) analysis method. The results of this study indicate that the variables of Budget Realization and Compliance Level of Annual Income Tax Report for Corporate Taxpayers have a significant positive effect for the short and long term on tax revenues. While the other variables do not have a significant positive effect on tax revenue.